The apprentices - Meloy, Maile (Puffin Books, 2014)
In 1954, Janie Scott has started boarding school in New Hampshire, but she often thinks about her friends, the apothecary and his son, Benjamin. On the other side of the world, Benjamin has become a doctor and is treating wounded soldiers in jungle warfare. Developing a magical way to communicate with Janie instantly has proved troublesome. More troublesome are the sinister forces moving in on Janie to take control of a new experiment of hers.